Distribusi Ikan pada Wilayah Genangan Berbeda di Danau Tempe, Sulawesi Selatan - Rahmi Dina; Eko Harsono; Gema Wahyudewantoro; Lukman; Riky Kurniawan; Agus Waluyo; Jojok Sudarso; Mey R.Widoretno, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Fish Distribution at Different Inundation Areas in Lake Tempe, South Sulawesi. Lake Tempe area consists of permanent standing watersand non-permanent area (flooded area). This study aims to investigate the species and its relative abundance distribution, as well as the distribution of size, condition factor, and gonad maturity stage of dominant species at those different areas. Sampling was carried at high water level period (March, June, and August 2017) in 18 stations, stations 1 to 13 represent the non-permanent inundation areas, and stations 14 to 18 represent the permanent inundation area. Fish was caught using various gears. Fish was identified morphologically and the number was counted. The size of the dominant species was measured and the gonad maturity stage was determined. Data were analyzed using descriptive and inferential statistics. The results of this study show that the highest number of species is found in non-permanent inundation areas. Species that are only found in non-permanent inundation areas are Clarias batrachus, Anabas testudineus, Pangasianodon hypopthalmus, and Trichopodus pectoralis. The dominant fish in the non-permanent inundation area are Oxyeleotris marmorata, Channa striata, Oreochromis niloticus, Trichopodus trichopterus, and Pterygoplichthys pardalis. These fishes have contributed significantly to capture fisheries production. The most abundant fish is Barbonymus gonionotus. The condition factor and the gonad maturity stage of the B. gonionotusin in the both areas were not significantly different. Larger fishes and higher relative abundance of B. gonionotus, when the water level was rising, were found in permanent inundation area. It can be concluded that the existence of those different inundation areas is important for fisheries productivity in Lake Tempe